Case report: Response to Savolitinib/EGFR-TKI combination in NSCLC patients harboring concurrent primary MET amplification/overexpression and EGFR mutation - Ren, Xiaolin; Li, Kejie; Zhang, Yang; Zou, Changlin; Su, Meng (Frontiers in Oncology, 2024)
Lung cancer is the leading cause of cancer death, accounting for one-third of all cancer deaths worldwide. MET (c-MET) gene as one of the therapeutic target spots of NSCLC has been more and more important. MET amplification/overexpression was divided into primary (intrinsic) and secondary (acquired). Studies indicated that the combination of Osimertinib and Savolitinib was safe and showed promising antitumor effect in NSCLC patients with secondary MET amplification after EGFR mutations. However, NSCLC patients with primary met amplification/ overexpression and EGFR mutations are rare in clinic, and the efficacy of dual-target therapy combined with EGFR-TKI and Savolitinib for them has not been studied yet. Here reported 2 NSCLC patients with primary met amplification/ overexpression and EGFR mutation, who benefited from T+S therapy (the dual-target therapy of EGFR-TKI plus Savolitinib) and achieved progression-free survival (PFS) of about 5 months. The two cases indicated that T+S therapy has an acceptable safety profile and encouraging anti-tumor efficacy in NSCLC patients harboring concurrent primary MET amplification/overexpression and EGFR mutation. Meanwhile, the observation stresses the importance of genetic testing, and MET gene needs to be detected at first diagnosis for the best choice of targeted therapies.